2022
DOI: 10.5267/j.ac.2021.6.007
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee chairman characteristics and corporate performance: Empirical evidence from Saudi Arabia

Abstract: The purpose of this paper is to investigate the impact of corporate governance (CG) characteristics, specifically audit committee chairman (ACC) characteristics. (tenure, expertise, and directorship) on corporate performance (CP). The study was executed on 44 firms, which were registered under the finance sector at Bursa Saudi Arabia. In terms of its scope, the study stretched over quite a long period of time and observed a considerable number of firms; more specifically, it lasted from 2015 to 2019, and obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The finding is against the theory and prediction in the beginning. The finding is in line with the previous studies disclosing that the audit committee meeting cannot improve the firm performance (Al-Matari, 2022;Bansal & Sharma, 2016;Borlea et al, 2017;Fauzi et al, 2017). This finding is due to the relatively small number of Indonesian companies in the sample meeting frequency.…”
Section: Hypothesis Testingsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding is against the theory and prediction in the beginning. The finding is in line with the previous studies disclosing that the audit committee meeting cannot improve the firm performance (Al-Matari, 2022;Bansal & Sharma, 2016;Borlea et al, 2017;Fauzi et al, 2017). This finding is due to the relatively small number of Indonesian companies in the sample meeting frequency.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Nevertheless, a negative association between CG and firm performance has been discovered (Meah et al, 2021;Suhadak et al, 2019). Meanwhile, (Al-Matari, 2022;Bansal & Sharma, 2016;Borlea et al, 2017;Fauzi et al, 2017) failed to discover a significant correlation between CG and firm performance. Therefore, the study is conducted to fill the gap between the earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the relationship between audit committee chair tenure. For instance, Al‐Matari (2022) found a positive impact of audit committee chair tenure on firm performance. Additionally, Gupta and Mahakud (2021) found that a longer tenure of audit committee members is positively correlated with performance and bank value.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…From the theory of agency perspective, the audit committee is considered a tool to improve the quality of monitoring information flow between those who own the entity and those who ensure its management (Forker, 1992). Similarly, Al-Matari (2013) predicts that audit committees that meet more frequently are better informed about the company's circumstances and provide a more effective oversight and monitoring mechanism of financial activities, which includes the preparation and reporting of company financial information. Anasweh (2021) concludes that in Islamic banks and conventional banks, audit committee meetings have a significant positive effect on firms' performance.…”
Section: Review Of Literaturementioning
confidence: 99%